The Influence of the Work Environment, Work Stress, and Work Motivation on the Performance of Employees of PT. Fuji Seimitsu Indonesia Plant 2 - Maira, Serlinda Nurhu; Gopar, Ida Abdul (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This study aims to determine the influence of Work Environment, Work Stress, and Work Motivation on the Performance of PT. Fuji Seimitsu Indonesia Plant 2. This type of research uses quantitative methods. The population in this study is employees of PT. Fuji Seimitsu Indonesia Plant 2 with a sample of 60 respondents using questionnaire data. This study uses non-probability sampling techniques with data analysis methods Validity Test, Reliability Test, Classical Assumption Test, Regression Analysis, and Hypothesis Test using partial. Based on the results of the T-Test (Partial) on work environment variables have a positive and significant effect with a calculated t value of 2,200 > t table 2,003 and a sig value. At 0.032 < 0.05, the work stress variable had a positive and significant effect with a calculated t value of 2,644 > t table 2,003 and a sig value. At 0.011 < 0.05, the work motivation variable had a positive and significant effect with a calculated t value of 5,253 > t table 2,003 and a sig value. A total of 0.000 < 0.05. Simultaneously, Work Environment, Work Stress, and Work Motivation have a significant effect on employee performance with F test results of sig values of 0.000 < 0.005.